Study for Murine Mammary Adenocarcinoma Implanted in Female Albino Mice for Evaluation of Antitumor Activity of Trigonella foenum graecum (Fenugreek) Seed Alkaloid Extract against Breast Cancer - Alaauldeen SM Al-Sallami (Journal of Global Pharma Technology, 2016)
The current study was designed to prepare the alkaloid extract of the Trigonella foenum graecum and studying the therapeutic potential of cancer in laboratory mice with a study of the physiological effect of the alkaloid extract, 48mice were used for studying, in the following groups (8 mice in each group) : The first group infused normal group injection with normal saline for 2 weeks and was considered a negative control group. The second group was its untreated tumor-bearing mice group for two weeks and was considered a positive control group. The third group was tumor-bearing mice treated using the 80 g / kg for 2 weeks. The fourth group was treated using alkaloids extract and 120 g / kg for 2 weeks. The fifth group was not infected with the tumor and was injected with the 80 g / kg alkaloids extract for 2 weeks. The sixth group was not infected with the tumor and was injected with the 120 g / kg alkaloids extract for 2 weeks. The results of the study showed that the tumor inhibition rate in the group rats treated with the plant extract 80 g / kg for two weeks was higher by significant difference (P <0.05) than the group treated with 120 g/kg alkaloids. The results of the CEA study and TP53 production showed a significant difference (P <0.0001) between the control groups and the treated and untreated tumor groups (positive control). No significant difference was found between positive control groups and tumor groups. The results of the physiological effect on the study groups showed higher levels of AST and ALT in tumor aggregates compared with control group but did not show significant differences between the groups injected with alkaloid extract only compared to the control group.Keywords: Fenugreek; Seed alkaloid extract; Trigonella foenum graecum; and female Albino mice.